MEMBACA KONSTRUKSI PERAN PEREMPUAN DALAM RUMAH TANGGA: Gambaran Konsep Hijrah dalam Kelompok Pengajian Kontemporer - ZAENUDIN AMRULLOH (TASÂMUH, 2019)
The recent hijrah trend is stealing the attention of middle class women in Indonesia. This trend is not new for Indonesia. The problem regarding some suggestions under the guise of religion guide which is discriminatory for Indonesian women has a long journey. However, nowadays, using the hijrah and halaqoh (group learning) trend can extend the age of discrimination against women with literal and closed religious values. This paper tries to give an idea of how women in the household are weakened by the use of inclusive literalist religion propositions. There are three implicit patterns in this halaqoh trend: hijab as a symbolic trend, internalization of women's values and functions in the household, and resistance of understanding. And this shows the incompatibility with the function of Islam as rahmatan lil 'alamin. How can Islam be a mercy if only women are weakened.